Avalia????o pedag??gica de alunos com necessidades educacionais especiais do munic??pio de Extrema: um estudo de caso - Almeida, Carla Campos de Oliveira (2017)
The evaluation of learning serves as a dynamic instrument of pedagogical practices, especially when the educational scenario It is crossed by the inclusion movement. The research proposal is to understand and reflect on the evaluative practices of regular teachers and elementary school teachers (1st to 5th year) of the municipality of Extrema ??? MG, of students with special educational needs. The research problem was delineated from concerns presented by the teachers who work with these students in the schools of the municipality, such as: how to evaluate students with SEN? What notes to assign? These questions led to the search for interlocutors directly involved with the problem, Mainly teachers from municipal schools who attended in regular education the largest number of students with SEN per class. It is about a case study. The work brings together reflections that emerged from the theoretical elaborated and analysis of the data obtained in teachers' reports and the questionnaires answered by them, As well as observations of everyday school life and also of the comparison with the guidance documents of the Municipal Department of Education that are included in the Municipal Plan of Education (2015 to 2024). The conclusions indicate conceptual tensions over the student with disabilities, Their possibilities of learning and their educational evaluation. The analysis of tensions leads to considerations, rather than to conclusions, that they intend to collaborate to deepen the discussions on such an important topic for educators who work with these students and, even more, for themselves.